Gastroenterology training in Australia: how much is enough?. Issue 4 (1st April 2013) - Leung, C.; De Cruz, P.; Jones, A.; Sliwka, G.; Bell, S. J.; Hebbard, G. S.
Abstract Background Advanced training in gastroenterology currently consists of 2 years of core training and 1 elective (non‐core) year. We surveyed gastroenterologists 2–7 years following completion of training to determine the strengths and weaknesses of their training. Methods All gastroenterologists were invited to participate in an anonymous online survey. Results There was a 46% response rate (49/110). Eighty‐one per cent were male with most aged 36–45. Respondents felt that the current training programme prepared them well for public practice and endoscopy but less well for private practice, ambulatory care, surgical aspects of gastroenterology and functional gastrointestinal disorders. Most had faced challenges transitioning to consultant practice. The majority (53%) spent more than the standard 3 years to complete training in gastroenterology. The top three subspecialty Fellowships were in endoscopy (45%), inflammatory bowel disease (29%) and hepatology (23%). In their elective year, 42% undertook a predominantly clinical year (registrar‐type position in general or subspecialty gastroenterology), 28% engaged in research while 24% trained in another specialty. Seventy‐eight per cent were in full‐time work, and 36% were supervising trainees. Ninety‐eight per cent felt that it was beneficial for trainees to move between hospitals during the core years of their advanced training. Conclusions The current Australian gastroenterology training programme is generally adequate in preparing trainees for consultant practice but could be improved by increased emphasis on areas such as private practice, ambulatory gastroenterology and functional gastrointestinal diseases. Exposure to a variety of experiences by training in several different hospitals during core training was universally viewed as being important.